Credit default swaps and corporate innovation - Chang, Xin (2020)
We show that credit default swap (CDS) trading on a firm's debt positively influences its technological innovation output measured by patents and patent citations. This positive effect is more pronounced in firms relying more on debt financing or being more subject to continuous monitoring by lenders prior to CDS trade initiation. Moreover, after CDS trade initiation, firms pursue more risky and original innovations and generate patents with higher economic value. Further analysis suggests that CDSs improve borrowing firms’ innovation output by enhancing lenders’ risk tolerance and borrowers’ risk- taking in the innovation process, rather than by increasing Research and Development (R&D) investment. Taken together, our findings reveal the real effects of CDSs on companies’ investments and technological progress.